2011
DOI: 10.17221/1576-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inorganic and organically bound forms of selenium on glutathione peroxidase activity in the blood of goats

Abstract: The goal of the experiment was to compare the effect of supplementation of inorganic and the new organically bound (lactate-protein selenium complex) form of selenium (Se) in feed for goats. The 31 goats were split into three groups: control (C) without Se supplementation, AN group administered sodium selenite, ORG group administered lactate-protein selenium complex (Selene Chelate, Agrobac, Czech Republic) produced by cultivation of Lactobacillus acidophilus on a substrate containing natrium selenite. The tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
2
17
1
Order By: Relevance
“…Also, in this case the group supplemented with the lactate-protein complex form reached the highest mean values (872.3 μkat/l) and the group supplemented with the selenite exhibited the lowest activity of this enzyme of all supplemented groups (659.5 μkat/l). This result is different from the previous experiment where the GSH-Px activity increased faster and more significantly after selenite supplementation (Pavlata et al, 2011).…”
Section: Selenium Supplementation Experimentscontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, in this case the group supplemented with the lactate-protein complex form reached the highest mean values (872.3 μkat/l) and the group supplemented with the selenite exhibited the lowest activity of this enzyme of all supplemented groups (659.5 μkat/l). This result is different from the previous experiment where the GSH-Px activity increased faster and more significantly after selenite supplementation (Pavlata et al, 2011).…”
Section: Selenium Supplementation Experimentscontrasting
confidence: 99%
“…Not all studies on administration of different forms of Se to goats clearly document a better biological effect of organic Se. For example, Pavlata et al (2011) reported that when comparing supplementation of selenite and a selenium lactate-protein complex there was a similar increase in the blood concentration in goats but in goats supplemented with inorganic Se there was a faster increase in the GSH-Px activity compared to the group supplemented with the lactate-protein complex. This can be explained by the higher and faster biological availability of Se supplied in selenite (for synthesis of seleniumdependent GSH-Px) compared to the Se which is part of the lactate-protein complex.…”
Section: Selenium Supplementation Experimentsmentioning
confidence: 99%
“…10 and 19 days after administration of the selenium supplement, respectively. In other studies (Andres et al 1996, Pavlata et al 2011, an increase in GSH-Px activity was observed 10-12 days after selenium supplementation. According to Philipoo et al (1987), GSH-Px activity is not enhanced directly the administration of selenium because selenium is first used to supplement tissue reserves, and it becomes involved in peroxidase synthesis only later.…”
Section: Selenium and Vitamin E Concentrations And Glutathione Peroximentioning
confidence: 68%
“…In newborn kids, however, a significant increase in blood Se levels and GSH-Px activity was observed only in the kids of mothers supplemented with sodium selenite. Pavlata et al (2011b) found in an experiment on goats, that the effects of supplementation with selenite and a lactate-protein selenium complex is similar from the standpoint of the ability to supply the organism with selenium, but that the speed of GSH-Px activity increase was better with selenite, which therefore appears to be a biologically better available form of selenium for the production of glutathione peroxidases -functional biologically active selenium proteins. Other authors, for example, Schrauzer (2000), reported that the utilisation of selenomethionine for GSH-Px synthesis also depends on methionine status.…”
Section: Discussionmentioning
confidence: 96%